(untitled) (Bangladesh Journal of Medical Science, 2025)
Introduction Globally, breastfeeding duration often falls short of recommendations, partly due to women becoming pregnant while still nursing. Although breastfeeding during pregnancy and tandem breastfeeding are supported, these practices lack widespread acceptance. Assessing women’s attitudes towards these practices is essential for promoting sustained breastfeeding, yet no standardized tool currently exists for this purpose. Objective This study aimed to develop a scale to evaluate women’s attitudes toward breastfeeding during pregnancy and tandem breastfeeding. Method An initial item pool was developed and refined using the Davis Technique. The scale was tested through two pilot studies (each with 100 participants), followed by a main study with 318 participants. The scale’s psychometric properties were assessed through validity and reliability analyses. Results and Conclusion The final scale is a five-point Likert-type instrument, explaining 50.01% of the total variance across two factors (breastfeeding during pregnancy and tandem breastfeeding) with 13 items. It demonstrated strong internal consistency with a Cronbach’s alpha of 0.87. BJMS, Vol. 24 No. 04 October’25 Page : 1228-1236